Plasmonic/magnetic liposomes based on nanoparticles with multicore-shell architecture for chemo/thermotherapy - Rodrigues, Ana Rita Oliveira (2022)
In this work, multicore magnetic nanoparticles (NPs) of manganese ferrite were prepared using carboxymethyl-dextran and melamine as agglutinating agents.Magnetoliposome-like structures containing the multicore NPs exhibit sizes in the range 250 – 400 nm, being suitable for biomedical applications.